The Scouting Extracurricular Student Learning Motivation for Physical Education Learning - Syahruddin, Syahruddin; Saleh, Muhammad Syahrul; Saleh, m Sahib (Journal of Sport Education, Coaching, and Health (JOCCA), 2023)
This study aims to determine how high the learning motivation of scouting extracurricular students towards physical education learning. This research is a quantitative descriptive research. The method used is the survey method. The subjects of this study were all students who participated in extracurricular scouting activities at SMA Negeri 13 Makassar totaling 31 students. The instrument used is a questionnaire. The analysis technique carried out is to pour frequency into percentages. The results showed that the learning motivation of scouting extracurricular students towards physical education learning in the high category was obtained by 11 students or 35.5%, in the medium category obtained by 15 students or 48.4%, in the low category obtained by 5 students or 16.1%. The results of this study showed that the learning motivation of scouting extracurricular students towards Physical Education learning was moderate with the consideration of the highest frequency being in the medium category with 15 students or 48.4%.